IMPLEMENTASI KEBIJAKAN ALOKASI DANA DESA (ADD) DI DISTRIK SINAK BARAT KABUPATEN PUNCAK PROVINSI PAPUA - Yafet Magai; Yosephina Ohoiwutun (Universitas Cenderawasih, 2021)
llage Fund Allocation is a policy issued by the government to spur development starting from the periphery, namely building from villages and villages. The hope is that with the Village Fund Allocation disbursed by the central government it can spur development growth and stimulate self-reliance and improve the standard of living of the community at the village or village level. Therefore, this study aims to describe and analyze the implementation of the Village / Village Fund Allocation policy in Sinak Barat District, Puncak Regency, Papua Province. As well as exploring the supporting and inhibiting factors in implementing the policy. Then the research method used is descriptive qualitative with data collection techniques in the form of interviews and observations. Then data analysis includes data reduction, data exposure, and drawing conclusions. The results show that if it is viewed from the aspect of communication and information dissemination has been carried out properly, with communication and coordination in each program agenda of the Village Fund Allocation. In the resource aspect, Sinak Barat District, Puncak Regency has an adequate quantity of resources and meets the sufficiency aspect, but in terms of quality it is still lacking. The disposition runs quite well based on the commitment and involvement of every institution at the village level. Then, the Bureaucratic Structure is based on the authority and responsibility given in accordance with their respective main tasks and functions. Then, the supporting factor is the high enthusiasm of the village community to be involved and participate in implementing the Village Fund Allocation policy. While the inhibiting factor is the problem of conflict which often hinders, because in the event of a conflict, the Village Fund Allocation budget is diverted to resolve the conflict. In addition, part of the budget is also earmarked for sudden health problems to treat people who are sick or dying, so the allocation of village funds for development becomes less effective.